Artificial Intelligence (AI) Driven Digital Dentistry (Update Dental College Journal, 2023)
The COVID-19 pandemic has brought significant changes to the way healthcare is delivered, including in the field of dentistry. Teledentistry, the practice of providing dental care remotely using digital technology, has become increasingly popular, and the use of Artificial Intelligence (AI) in teledentistry has emerged as an important tool for dental care, education, and research. AI algorithms are being utilized to assist in the diagnosis, treatment planning, and prediction of treatment outcomes in various dental branches, including operative dentistry, periodontics, prosthodontics, and orthodontics. With the ability to simulate treatment outcomes and identify abnormal spots in radiographs, AI is transforming dentistry from a curative to a personalized predictive and preventive paradigm.Update Dent. Coll. j: 2023; 13(1): 1-2